"I'm a completely different person now": Extraordinary experiences and personal transformations in sport. Issue 4 (August 2020) - Rundio, Amy; Dixon, Marlene A.; Heere, Bob
Highlights: Extraordinary experiences in sport can result in lasting personal transformation. Newness, intense emotions and deep interpersonal connections led to transformations. Participants developed a sense of empowerment and new meaning and purpose in life. Abstract: Many sport programs aim to positively impact participants' lives, but there is little understanding of how sport leads to those changes. The purpose of this study was to examine an extraordinary experience and the participants' interpretations of that experience as well as their feelings of personal transformation through the experience. In doing so, the authors developed an understanding of how sport can be used to create meaningful life changes at the individual level. Semi-structured interviews were conducted with 32 past participants of a long distance cycling ride that raised money and awareness for cancer research. Data analysis included three rounds of coding. Participants reported that the unusualness and sense of newness of the ride, the high levels of emotional intensity experienced, and the deep interpersonal connections developed led to a sense of empowerment and new meaning and purpose in life. Results indicate that extraordinary experiences contribute to lasting personal transformations, beyond intended behavior changes, within sport and out of sport. The characteristics of extraordinary experiences that contribute to personal transformation are discussed, as are suggestions for sport managers to leverage extraordinary experiences to create positive personal transformations.